2020
DOI: 10.3389/fevo.2020.571454
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory and Visual Floral Signals of Hedera helix and Heracleum sphondylium Involved in Host Finding by Nectar-Foraging Social Wasps

Abstract: Social vespid wasps regularly forage on flowers with a generalist pollination system. However, little is known about communication between wasps and their host plants. The aim of this study was to investigate the role of olfactory and visual floral signals of Hedera helix and Heracleum sphondylium, both frequently visited by Vespula and Dolichovespula wasps for the collection of nectar. A combination of chemical, electrophysiological and spectral analyses and behavioral experiments was used to identify attract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 83 publications
(124 reference statements)
1
7
1
Order By: Relevance
“…terfly Pieris brassicae exhibited a strong bias for optical cues over volatile chemical cues when both cues were offered separately, in agreement with studies on host location by insect pollinators, in which many pollinators exhibit feeding behaviour in response to colour stimuli (Van der Kooi et al, 2021). In contrast, other studies have reported that chemical cues are more important than optical cues to attract pollinators from a distance (Raguso, 2008;Primante and Dötterl, 2010;Lukas et al, 2020). However, insect pollinators exploit visual and odour information simultaneously, thus optical and chemical plant traits both contribute to foraging pollinator preferences (Raguso and Willis, 2002;Milet-Pinheiro et al, 2012;Chapter 2).…”
Section: Plant Phenotypic Plasticity In Response To Aboveground Inter...supporting
confidence: 85%
“…terfly Pieris brassicae exhibited a strong bias for optical cues over volatile chemical cues when both cues were offered separately, in agreement with studies on host location by insect pollinators, in which many pollinators exhibit feeding behaviour in response to colour stimuli (Van der Kooi et al, 2021). In contrast, other studies have reported that chemical cues are more important than optical cues to attract pollinators from a distance (Raguso, 2008;Primante and Dötterl, 2010;Lukas et al, 2020). However, insect pollinators exploit visual and odour information simultaneously, thus optical and chemical plant traits both contribute to foraging pollinator preferences (Raguso and Willis, 2002;Milet-Pinheiro et al, 2012;Chapter 2).…”
Section: Plant Phenotypic Plasticity In Response To Aboveground Inter...supporting
confidence: 85%
“…However, there are recent studies that describe 4-oxoisophorone as floral scent component in a broader range of species (e.g. El-Sayed et al, 2018;Lukas et al, 2019Lukas et al, , 2020. Future studies should test how A. vaga bees behaviourally respond to 1,4-dimethoxybenzene and 4-oxoisophorone when they are offered simultaneously, and to which extent these two compounds may be synergistically involved in host recognition.…”
Section: Olfactory Cues Of Hosts and 4-oxoisophorone Are Highly Attractivementioning
confidence: 99%
“…In three highbush blueberry (Vaccinium corymbosum) cultivars, oral scents are dominated by (E)-cinnamyl alcohol ( 154), but various aliphatic compounds and terpenes also are released. 312 Finally, one study tested for correlations between oral volatiles of greenhouse tomato (Lycopersicon esculentum, Solanaceae) and pollination by bumblebees. 313 Tomato owers released b-phellandrene (201), 2-carene ( 202), a-pinene (72) and p-cymene (106), and bumblebees preferably pollinated owers that produced less 201 and 202 than owers producing more of these compounds.…”
Section: Reviewmentioning
confidence: 99%
“…, ( E )-β-ocimene ( 62 ), 4-oxoisophorone ( 169 )], but also rare [ N -isobutylformamide ( 199 ), ( E )- N -(3-methylbutyl)-1-phenylmethanimine ( 200 )] floral scents and even compounds newly identified from nature [( E )- N -(2-methylbutyl)- and ( E )- N -(3-methylbutyl)-1-(pyridin-3-yl)methanimine ( 46 and 47 )]. 312 …”
Section: Floral Volatiles As Attractants For Flower Visitorsmentioning
confidence: 99%
See 1 more Smart Citation